Impacto del covid-19 en los componentes Bio - Psico - Socio familiar de un grupo de adolescentes. (2023)
The research arises from the impact of Covid -19 on a group of adolescents, focusing on three main elements: Bio, Psycho and Family Partner. The appearance of Covid-19 occurred in China and has spread to millions of countries, so much so that the WHO on January 30, 2020 classified the outbreak as a global health emergency with an increasing growth in many countries.